Fluid Intake and Hydration among Children - Fitria Saftarina; Milatul Fauziah (Review of Primary Care Practice and Education (Kajian Praktik dan Pendidikan Layanan Primer), 2023)
Children birth a greater chance of desiccation than adults. As many as 22% of children in Indonesia calm do not drink plenty. As a resolution of many studies, children came to school with a shortage in hydration prominence. Objectives: The purpose of this study are describe fluid intake and  hydration state among children at elementary school in Lampung. Methods: Design of this study used analytical observational study. The sampel was 69 children, with total sampling technique. The study was conducted from Sept 2019 to Jan 2020, at  primary school in Bandar Lampung. Fluid intake was obtained  from the Beverage Uptake Questionaire and hydration state was obtained from urine specific gravity. Results: The result of study,  a total 48 children (69,6) had good fluid intake, 47 children (68,1%) drinking water more than  3 times a day but 42 children (60.9%) had clinical dehydration. Conclusion: Further research is needed to measure adequacy of fluid intake with other methods and instruments.